Management of Marine Fish Inventory at Fish Auction Place in Tenda Village, Hulonthalangi District, Gorontalo City - Hartati Tuli (PT. EQUATOR SINAR AKADEMIA, 2022)
This research aims to improve the welfare of the people of Gorontalo through the application/development of ways to maintain the existence of their business by managing inventory properly and correctly in accordance with applicable standards. The specific objective to be achieved is to find out how to manage marine fish stocks at the Fish Auction Place (TPI) located in the Tenda village, Hulonthalangi sub-district, Gorontalo City. This study uses a qualitative method by using interviews and observations as stages in data collection. From the results of the research that has been carried out, it shows that the management of marine fish stocks at TPI has been going well because of a good work system among all people involved in the Gorontalo Marine Fish Auction Place and good management of the fish stock caught